L-Theanine: A Unique Functional Amino Acid in Tea (Camellia sinensis L.) With Multiple Health Benefits and Food Applications - Li, Ming-Yue; Liu, Hong-Yan; Wu, Ding-Tao; Kenaan, Ahmad; Geng, Fang; Li, Hua-Bin; Gunaratne, Anil; Li, Hang; Gan, Ren-You (Frontiers in Nutrition, 2022)
Tea (Camellia sinensis L.) is a very popular health drink and has attracted increasing attention in recent years due to its various bioactive substances. Among them, L-theanine, a unique free amino acid, is one of the most important substances in tea and endows tea with a special flavor. Moreover, L-theanine is also a bioactive compound with plenty of health benefits, including antioxidant, anti-inflammatory, neuroprotective, anticancer, metabolic regulatory, cardiovascular protective, liver and kidney protective, immune regulatory, and anti-obesity effects. Due to the unique characteristics and beneficial functions, L-theanine has potential applications in the development of functional foods. This review summarized the influencing factors of L-theanine content in teas, the main health benefits and related molecular mechanisms of L-theanine, and its applications in food, understanding of which can provide updated information for the further research of L-theanine.